Internationalization performance revisited: the impact of age and speed on sales growth - Verdier, Sylvie; Prange, Christiane; Atamer, Tugrul; Monin, Philippe (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2010)
Internationalization process theories have been dominated by the Uppsala theory and the new venture theory: they provide explanations for slow international growth by mature firms and fast international growth by young firms, but fail to consider other combinations of age and speed. This article sketches a 2*2 matrix and explores the performance differentials of four internationalization patterns. Building on early empirical evidence from the retailing industry (1998-2004), the combination of young and slow internationalization is preferable to other options, while a young age is generally more likely to yield internationalization performance than any combination of mature internationalization with slow or accelerated speed.